Technologies of interactive English teaching at technical universities - Svetlana I. Linnichenko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The interactive learning is the mandatory requirement in the Federal State Educational Standard of Higher Education. Language skills are necessary for high-qualified specialists in different fields including the technical sphere. Therefore, the new interactive methods of teaching a foreign language should be developed. The goal of the study was to theoretically substantiate and experimentally test the pedagogical conditions and implementation forms of interactive teaching a foreign language at technical university. As research tools, we used methods of literature review, theoretical analysis of pedagogical literature, and generalization of scientific data. It is concluded that in the educational practice such forms of interactive learning as creative tasks, educational games, work in groups, projects and e-Learning are used. As a result of the study, there have been proposed pedagogical conditions for implementing interactive language teaching; besides, there have been studied the educational resources of the interactive forms; the created and tested author's educational and methodological materials based on the platforms Quizlet and Worldwall.net were intended for the effective organization of students independent work in an interactive mode. The study concluded that interactive methods and techniques develop language skills, but by teaching a foreign language in modern conditions, a competent combination of traditional academic forms and interactive, including electronic forms, is required.